Extended-spectrum beta lactamasa-producing Enterobacteriaceae: The current situation in Latin America and Peru - García, Coralith (2012)
Enterobacteriaceae, particularly E. coli and Klebsiella spp. show an increasing resistance to cephalosporins all over the world. There very few studies in Peru about this situation. This paper tries to perform a scientific evidence based review about this increasingly serious problem.